Latitude, temperature, and habitat complexity predict predation pressure in eelgrass beds across the Northern Hemisphere. Issue 1 (4th January 2018) - Reynolds, Pamela L.; Stachowicz, John J.; Hovel, Kevin; Boström, Christoffer; Boyer, Katharyn; Cusson, Mathieu; Eklöf, Johan S.; Engel, Friederike G.; Engelen, Aschwin H.; Eriksson, Britas Klemens; Fodrie, F. Joel; Griffin, John N.; et al.
Abstract: Latitudinal gradients in species interactions are widely cited as potential causes or consequences of global patterns of biodiversity. However, mechanistic studies documenting changes in interactions across broad geographic ranges are limited. We surveyed predation intensity on common prey (live amphipods and gastropods) in communities of eelgrass ( Zostera marina ) at 48 sites across its Northern Hemisphere range, encompassing over 37° of latitude and four continental coastlines. Predation on amphipods declined with latitude on all coasts but declined more strongly along western ocean margins where temperature gradients are steeper. Whereas in situ water temperature at the time of the experiments was uncorrelated with predation, mean annual temperature strongly positively predicted predation, suggesting a more complex mechanism than simply increased metabolic activity at the time of predation. This large‐scale biogeographic pattern was modified by local habitat characteristics; predation declined with higher shoot density both among and within sites. Predation rates on gastropods, by contrast, were uniformly low and varied little among sites. The high replication and geographic extent of our study not only provides additional evidence to support biogeographic variation in predation intensity, but also insight into the mechanisms that relate temperature and biogeographic gradients in species interactions.